Extended Abstracts of the 1992 International Conference on Solid State Devices and Materials 1992
DOI: 10.7567/ssdm.1992.pd1-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Visible Photoluminescence from μc-Ge Embedded in SiO2 Glassy Matrices

Abstract: The origin of visible photoluminescence of Ge microcrystals (pc-Ge) in SiOz glassy matrices was examined. The spectroscopic analyses and formation mechanism show that the origin of strong light emission with nanosecond decay time is attributed to the effective surface termination and the new nanostructure of pc-Ge with diameter less than 4 nm which forms from reduction reaction of germanium oxides at low annealing temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As a result of the small band gap of Ge, electron–hole recombination in GeNCs is expected to exhibit PL in the NIR or IR spectral regions. However, reports are often contradictory regarding the source of PL, critical NC size, expected PL wavelength, quantum yield, effect of oxides and other impurities. ,,,, Adding further complexity, germanium oxides can often show visible PL. , There are also numerous examples showing UV–vis emitting GeNCs, ,, however it has been suggested that these emitters likely show PL resulting from surface species (e.g., oxides) rather than quantum confinement of GeNCs. ,− There are surprisingly few examples of colloidal GeNCs showing NIR or IR PL. ,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the small band gap of Ge, electron–hole recombination in GeNCs is expected to exhibit PL in the NIR or IR spectral regions. However, reports are often contradictory regarding the source of PL, critical NC size, expected PL wavelength, quantum yield, effect of oxides and other impurities. ,,,, Adding further complexity, germanium oxides can often show visible PL. , There are also numerous examples showing UV–vis emitting GeNCs, ,, however it has been suggested that these emitters likely show PL resulting from surface species (e.g., oxides) rather than quantum confinement of GeNCs. ,− There are surprisingly few examples of colloidal GeNCs showing NIR or IR PL. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Despite the average size of the functionalized GeNCs investigated here being smaller than the Bohr-exciton radius of Ge (i.e., 24.3), , they do not show detectable PL. We hypothesize that this may result from dark surface defects (e.g., impurities, vacancies, surface oxides, dangling bonds, and so forth) arising from the HF liberation protocol that remain after hydrogermylation that provide nonradiative pathways. ,, In an effort to passivate potential (as of yet unidentified) defects on the GeNC surfaces, we introduced a trace quantity of I 2 into the hydrogermylation reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation